From Eshu to Obatala: animals used in sacrificial rituals at Candomblé "terreiros" in Brazil - Brooks Sharon E; Alves Rômulo RN; Léo Neto Nivaldo A (BMC, 2009)
Abstract Background The practice of sacrifice has occurred in several cultures and religions throughout history and still exists today. Candomblé, a syncretical Afro-Brazilian religion, practices the sacrificial ritual called "Orô" by its adherents. The present work aims to document the use of animal species in these sacrificial practices in the cities of Caruaru (PE) and Campina Grande (PB) in Norteastern Brazil, and to further understand the symbolism of these rituals. Methods Semi-structured and unstructured interviews and informal discussions were held with 11 Candomblé priests and priestesses between the months of August 2007 and June 2008. We attended rituals performed at "terreiros" where animals were sacrificed, in order to obtain photographic material and observe the procedures and techniques adopted. Results A total of 29 animal species were used during sacrificial rituals according to the priests and priestesses. These species were classified in 5 taxanomic groups: Molluscs (n = 1), Amphibians (n = 2), Reptiles (n = 2), Birds (n = 10) and Mammals (n = 14). According to Candomblé beliefs, animals are sacrificed and offered to their deities, known as orishas, for the prosperity of all life. There is a relationship between the colour, sex and behaviour of the animal to be sacrificed, and the orisha to whom the animal is going to be offered. The many myths that form the cosmogony of Candomblé can often explain the symbolism of the rituals observed and the animal species sacrificed. These myths are conveyed to adherants by the priests and priestesses during the ceremonies, and are essential to the continuation of this religion. Conclusion Candomblé is a sacrificial religion that uses animals for its liturgical purposes. The principal reason for sacrifice is to please supernatural deities known as orishas in order to keep life in harmony. This is accomplished through feeding them in a spiritual sense through sacrifice, maintaining a perfect link between men and the gods, and a connection between the material world (called Aiyê) and the supernatural world (called Orun).